Food Nutrition Analysis For Health Using Data Mining Techniques - Kayalvily, Tabianan; Sia, Zi Siang (INTI International University, 2020)
Nowadays, manufactured food is used in most of our diet, which is related to food nutrition. Food Nutrition system is a concept widely used but there is little systematic framework that can model the entire food nutrition system. Processing on the structure and composition of food has a major impact on the nutritional value. If adolescents consume a large amount of the super processed food, they risk a rise in obesity and diabetes. As such, the author developed a system using Data Mining Techniques to improve the food nutrition values for users. It helped to identify the habits of the teenagers and their ability to make decisions. Furthermore, this project was aimed at investigating the role and relationship among food, health and the environment, as well as their chronic micronutrient deficiency (also known as “hidden hunger”).